When It Comes to Business, the Right and Left Sides of the Court Agree - Lee Epstein; William M. Landes; Richard A. Posner (Washington University Journal of Law & Policy, 2017)
This Article analyzes the voting trends among both liberal- and conservative-leaning Supreme Court justices in the Roberts Court in cases where corporations are a party on one side, either as petitioner or respondent. Epstein, Landes, and Posner show that business interests have had a strong presence in front of the Roberts Court, and in most cases, the Court has voted in favor of businesses. The Article notes that current liberal-leaning Justices are still less pro-business than their conservative colleagues, but Clinton/Obama-appointed liberals on the Roberts Court are still more pro-business than their Democratic predecessors appointed by previous presidents. The authors conclude the trends leading up to and supported by the Roberts Court characterize the bench as “pro-business.”
Keywords: Supreme Court; Ideology; Business Interests; Roberts Court; Pro-business; Voting